2018
DOI: 10.1159/000488796
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Gastric Black Spot, White Flat Elevated Mucosa, and Cobblestone-Like Mucosa: A Cross-Sectional Study

Abstract: Background/Aims: Previous studies have reported a possible relevance between proton pump inhibitor (PPI) use and 3 new gastric mucosal changes: black spots (BSs), white flat elevated mucosa (WFEM), and cobblestone-like mucosa (CLM). The aim of this study was to investigate the association between these mucosal changes and multiple factors including PPI use. Methods: All subjects who underwent a routine esophagogastroduodenoscopy (EGD) were successively enrolled. Endoscopists carried out the EGD after being bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…38 In a cross-sectional study, multivariate analyses showed that the cobblestone-like mucosa was associated with PPI use (OR, 4.57; 95% CI, 2.34 to 9.96) and diabetes mellitus (OR, 3.41; 95% CI, 1.47 to 7.91). 12 A prospective, multicenter study also showed that the cobblestone-like mucosa was associated with PPI use (OR, 13.72; 95%, CI, 5.49 to 35.28), sex (female: OR, 0.32; 95% CI, 0.09 to 0.89), and age of the patients (≥50 years: OR, 4.46, 95% CI, 1.15 to 29.49). 10 Cobblestone-like mucosa has been histopathologically characterized by PCP and cystic dilatation of fundic glands, and these changes are especially prominent in non-atrophic gastric regions with abundant fundic glands.…”
Section: Cobblestone-like Mucosamentioning
confidence: 94%
See 2 more Smart Citations
“…38 In a cross-sectional study, multivariate analyses showed that the cobblestone-like mucosa was associated with PPI use (OR, 4.57; 95% CI, 2.34 to 9.96) and diabetes mellitus (OR, 3.41; 95% CI, 1.47 to 7.91). 12 A prospective, multicenter study also showed that the cobblestone-like mucosa was associated with PPI use (OR, 13.72; 95%, CI, 5.49 to 35.28), sex (female: OR, 0.32; 95% CI, 0.09 to 0.89), and age of the patients (≥50 years: OR, 4.46, 95% CI, 1.15 to 29.49). 10 Cobblestone-like mucosa has been histopathologically characterized by PCP and cystic dilatation of fundic glands, and these changes are especially prominent in non-atrophic gastric regions with abundant fundic glands.…”
Section: Cobblestone-like Mucosamentioning
confidence: 94%
“…2C). 12,25 These lesions are usually found in the upper gastric corpus and fundus, and close observation allows identification of tubular structures on their surface (Fig. 2D).…”
Section: Multiple White and Flat Elevated Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Another artificial intelligence system, namely convolutional neural network (CNN), was also constructed to ascertain H. pylori infection status. 13 White opaque substance, an endoscopic marker of intestinal metaplasia visualized by magnifying NBI, was shown to be associated with gastric acidity. Using an algorithm, an accuracy of 80% was obtained for H. pylori negative status, 84% for posteradication status, but only 48% for H. pylori positive status, within a lapse time of 261 seconds.…”
mentioning
confidence: 99%
“…12 Another study confirmed the association of gastric black spots with H. pylori eradication and PPI and also found white flat elevated mucosa and cobblestone-like mucosa associated with PPI use. 13 White opaque substance, an endoscopic marker of intestinal metaplasia visualized by magnifying NBI, was shown to be associated with gastric acidity. Indeed, strong acidity inactivates the lipase which plays a role in the lipid absorption process.…”
mentioning
confidence: 99%